Secure Shell in the Enterprise - Reid, Jason (Pearson, 2003)
The best practices guide to building, scaling and deploying Open SSH for legacy Solaris (2.6, 7, and 8) and Solaris 9 OE systems. Covers the new Solaris Secure Shell for all versions of Solaris. Shows how to secure remote logins, integrate Secure Shell into existing scripts and avoid common problems. Written by Jason Reid, a member of the Solaris System Test group at Sun Microsystems, Incorporated.
Online resource; Title from title page (viewed June 12, 2003)
Keywords: Solaris (Computer file); UNIX Shells; Operating systems (Computers); Computer networks -- Security measures; Systèmes d'exploitation (Ordinateurs); Réseaux d'ordinateurs; Sécurité; Mesures; operating systems; Computer networks; Security measures